Exploring the use of Artificial Intelligence and Augmented Reality tools to improve interactivity in Physical Education teaching and training methods - Shirinkyz Shekerbekova; Guldina Kamalova; Makpal Iskakova; Aigul Aldabergenova; Elmira Abdykerimova; Karlygash Shetiyeva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The advent of AI and augmented reality revolutionizes physical education by offering engaging, interactive methods and immersive experiences that boost student motivation and learning outcomes.